Analisis Pengaruh Ekspor Halal, Foreign Direct Investment, Trade Openness, Nilai Tukar, Dan Pertumbuhan Populasi Terhadap Produk Domestik Bruto Riil Asean - Cupian, Cupian; Noven, Sarah Annisa; Smitasari, Daneswara (ITB AAS INDONESIA Surakarta, 2024)
This study aims to determine the effect of halal exports, foreign direct investment (FDI), trade opennes, exchange rates and population growth on real gross domestic product in ASEAN countries from 2010 to 2021. Using panel data regression from ASEAN countries; Indonesia, Malaysia, Singapore, Thailand, Brunei Darussalam, Vietnam, Cambodia, Laos, Philippines and Myanmar. The study shows that the halal food export variable to OIC countries has a significant positive effect on real GDP in ASEAN countries, the foreign direct investment (FDI) variable has an insignificant positive effect on real GDP in ASEAN countries, the other variable such as the trade openness, the population variable has a significant positive effect on real GDP in ASEAN countries, menawhile the exchange rate variable has a significant negative effect on real GDP in ASEAN real gross domestic product 2010-2021.